2011
DOI: 10.1146/annurev-physchem-032210-103512
|View full text |Cite
|
Sign up to set email alerts
|

Simulating Chemistry Using Quantum Computers

Abstract: The difficulty of simulating quantum systems, well-known to quantum chemists, prompted the idea of quantum computation. One can avoid the steep scaling associated with the exact simulation of increasingly large quantum systems on conventional computers, by mapping the quantum system to another, more controllable one. In this review, we discuss to what extent the ideas in quantum computation, now a well-established field, have been applied to chemical problems. We describe algorithms that achieve significant ad… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
326
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 305 publications
(336 citation statements)
references
References 136 publications
(168 reference statements)
0
326
0
1
Order By: Relevance
“…Particularly significant is the exponential speed up achieved for the prime factorization of large numbers [3], a problem for which no efficient classical algorithm is currently known. Another attractive area for quantum computers is quantum simulation [4][5][6][7][8][9] where it has recently been shown that the dynamics of chemical reactions [10] as well as molecular electronic structure [11] are attractive applications for quantum devices. For all these instances, the realization of a quantum computer would challenge the Extended Church-Turing thesis (ECT), which claims that a Turing machine can efficiently simulate any physically realizable system, and even disprove it if prime factorization was finally demonstrated to be not efficiently solvable on classical machines.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly significant is the exponential speed up achieved for the prime factorization of large numbers [3], a problem for which no efficient classical algorithm is currently known. Another attractive area for quantum computers is quantum simulation [4][5][6][7][8][9] where it has recently been shown that the dynamics of chemical reactions [10] as well as molecular electronic structure [11] are attractive applications for quantum devices. For all these instances, the realization of a quantum computer would challenge the Extended Church-Turing thesis (ECT), which claims that a Turing machine can efficiently simulate any physically realizable system, and even disprove it if prime factorization was finally demonstrated to be not efficiently solvable on classical machines.…”
Section: Introductionmentioning
confidence: 99%
“…In case of the C-H bond stretching, we were using the CASCI with 6 electrons in 12 orbitals [CAS (6,12)]. This leads to roughly 4300 configuration state functions (CSFs) in the aforementioned compact mapping.…”
Section: A Computational Detailsmentioning
confidence: 99%
“…We will mention only some of them and for a complete list refer the reader to recent reviews [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…An exponential growing interest of the scientific community started since on. Therefore, many quantum algorithms have been proposed to simulate quantum systems [98][99][100][101][102][103][104] which have an exponential speed-up with respect to any equivalent classical algorithm. More importantly, in the last few years, the first quantum devices with quantum capabilities have been devised [105][106][107][108], showing that quantum computing is not merely an academic exercise.…”
Section: Constant On Quantum Computersmentioning
confidence: 99%